KUALITAS TINGKAT PELAYANAN MINIMUM TERMINAL KARGO DOMESTIK BANDAR UDARA - Subekti, Sitti; R. Agah, Heddy; Widjajanti, Endang (Jurnal Transportasi, 2012)
Quality of cargo management services is primary consumer expectation indicator measured by the dimension model and the minimum service time. Likert scale of five levels is use, analyzed with Important Performance Analysis and Performance Analysis Approach to portray the user perception and expectation. Five dimensions of quality aspect are selected such as reliability, responsiveness, assurance, empathy, and physical evidence. Two air cargo companies operating at Jakarta International Airport Soekarno Hatta are selected as respondents with sample sizes of 46 and 33 are observed. A grid with four quadrants is developed. The result shows that the two operator need improvement to reach minimum service time of 30 minutes. The existing system is in a range between 46 to 51.51 minutes to finish all system services steps. To reach the minimum service time, the operator management, equipment, and tools must be improved.Keywords: Domestic terminal, cargo, service quality, Importance Performance Analysis